(untitled) (Revista Brasileira Multidisciplinar, 2015)
This text celebrates Araraquara’s birthday, in August, on the eve of its second centenary (1817-2015). It is a homage to its expressive cultural heritage, highlighting artistic and intellectual aspects of its history in the first half of the last century. Considering this, it rescues the extraordinary development in two important areas: theater and plastic arts, emphasizing the singularity of these manifestations and the main involved protagonists. Deepening the historical view, it also captures some contradictions.